Flower induction of coffee trees under different irrigation managements - Custódio, Anselmo Paiva; Rezende, Fátima Conceição; Faria, Manoel Alves; Morais, Augusto Ramalho; Guimarães, Rubens José; Scalco, Myriane Stela (Coffee Science - ISSN 1984-3909, 2012)
The objective of this work was to evaluate the effect of different irrigation managements on flower induction and bloom of coffee trees. The study was carried out at the experimental area of the Engineering Department at Universidade Federal de Lavras, on Acaia Cerrado MG-1474 coffee cultivar, planted 3.0 meters between rows and 0.6 meters between plants and drip irrigated since planting in 1997. The experimental design was randomized blocks with 4 replicates and 5 irrigation treatment: A= non irrigated; B= irrigated throughout the whole year every time the water available was at most 25% of total available water (TAW); C= irrigated during the whole year every time the water available was at most 75% of TAW; D= treatment C during January, February, March, July, October, November and December and treatment B during April, May, June, August and September; E= treatment C during April, May, June, August and September. Each plot was composed of 10 plants and used 2 plants for the evaluation of secondary branches, number of flowers per flowering, number of fruit and fruit set between September and May during the growing seasons of 2006/2007 and 2007/2008. The different irrigation managements did not significantly influence the total number of flowers, number of branches and percentage of flowers that resulted in fruits. Comparing data from two harvests verified the biennial effect in the total number of flowers, percentage of fruit set and branch gain.